Strategi Badan Pengawas Pemilu Dalam Mengawasi Kualitas Pelayanan Kelompok Disabilitas Pada Penyelenggaraan Pemilihan Kepala Daerah Serentak 2020 Di NTB - Aisyah Aisyah; Amil Amil; Yudhi Lestanata; Ilham Zitri (Universitas Muhammadiyah Mataram, 2025)
The strategy of the Election Supervisory Agency in supervising the quality of services for groups with disabilities in the implementation of the 2020 Simultaneous Regional Elections in NTB is one of the obligations to realize democratic election rights. This study aims to determine the strategy of the NTB Provincial Election Supervisory Agency in supervising the quality of services for groups with disabilities in the 2020 Simultaneous Regional Elections in NTB and to determine the factors that influence the implementation of strategies for the quality of services for groups with disabilities in the implementation of the 2020 Simultaneous Regional Elections in NTB. The research method used is qualitative with a descriptive analysis approach. Data were obtained through interviews and literature studies. The results of the study show that the strategy of the Election Supervisory Agency in supervising the quality of services for groups with disabilities in the 2020 Simultaneous Regional Elections in NTB has three aspects. The first aspect determines the long-term formulation, the second aspect selects a series of actions, the third aspect determines the allocation of resources, and shows that the factors that influence the implementation of the Election Supervisory Agency's strategy are communication factors and resource factors.